Just war and nuclear weapons : just war theory and its application to the Korean nuclear weapons issue in Korean Christianity - Son, Changwan (The University of Edinburgh, 2009)
This thesis is primarily an application of the Christian tradition of Just War to the problems arising from the basing of US nuclear weapons in South Korea and the development of nuclear weapons by the regime in the North. The Christian theology of Just War has developed over the last two thousand years, adapting as first Christianity became the state religion of the Roman Empire, through the break down of any enforceable norms in Europe‘s 'Dark Ages‘, to the emergence of the concept of the modern nation state at the end of the Thirty Years Wars in 1648. Throughout these shifts, two issues have remained constant, although their relative weight has changed. First that a war can only be described as 'just' if it is being waged for legitimate reasons, jus ad bellum, and that is waged in a proportionate manner that seeks to separate combatants from non-combatants, jus in bello. Both these ideas were severely weakened in the period of warfare that followed on from the American and French Revolutions at the end of the Eighteenth Century. The new ideology of nationalism brought with it the idea of the nation at arms, the armed citizenry, and with this, a further blurring of the always weak distinction between soldiers and the wider population. By 1945, both the secular and Christian tradition lay in ruins, damaged by the total warfare in the twentieth century when anything and anyone who could contribute to the wider war effort became a target. Also, although not the most destructive weapon, this saw the advent of the nuclear bomb. In response, Christian thinkers sought to redefine the concepts of Just War for a nuclear age, with the potential for the use of weapons that could destroy all of humanity. Some saw this as the lesser evil, when faced with the victory of a totalitarian political system, and others argued that proportionality could be maintained if the size of weapons, or their targeting, was such as to minimise wider damage. On the other hand, many theologians argued that by definition they could never be discriminate or proportionate and that their use (or even the implied threat of their use) would always fail the precepts of Jus in Bello. In the modern Korean context, this debate is not abstract, but has real bearing on the practical steps being taken by all the main parties. The acquisition of nuclear weapons by the North (the DPRK) has meant that the desire for Korean re-unification has become entwined with how best to resolve the nuclear issue. At the moment, in the South amongst the Protestant communities (split between the CCK and the NCCK), this debate has become fixed on issues of practical politics. In effect, is it better to negotiate with the North over the nuclear weapons issue and hope that resolving this will then lead to reunification or is it better to aim to overthrow the DPRK (economically, politically or even militarily) and, this, by definition, would resolve the question of their possession of nuclear weapons. At the moment both the NCCK and the CCK have based their policies towards North Korea (the DPRK) on the basis of secular politics not the teachings of the Christian gospel. The NCCK is tending to overlook human rights abuses in the DPRK, and the threat of that regime‘s nuclear arsenal, in their emphasis on the need to overcome the political division of Korea. In turn, the CCK ignores much Christian teaching with its emphasis on seeking the collapse (perhaps by military means) of the DPRK as a precursor to unification. In this, both bodies seem to have forgotten that they are fundamentally Christian confessional bodies, and as such their public statements should be based on the Gospels, not on the practicalities of day to day politics. Neither approach is particularly grounded on either in the Christian message of the gospels or the Just War tradition. Thus this thesis does not just seek to explore and explain the current situation in Korea using the concepts of Just War, it also seeks to provide a basis on which the Protestant community can resolve their current impasse. This means the thesis is grounded on the Christian concept of political theology, in particular in so far as this approach 'offers alternatives to better comprehend the different postures and approaches towards a solution‘. In the case of the situation in Korea, this means there is no military solution to the problem of unification. Nor can a solution be found in ignoring the human rights abuses in the DPRK. The answer lies in stressing three aspects that remain fundamental to any Christian identity in Korea – of a unified Korean koinoina, that any resort to force must meet the conditions of the Christian Just War tradition, and that, as faith groups, any response must stem from the Gospels.
Keywords: just war; nuclear weapons; North Korea; Korean church